Secondary rhinoplasty: reconstitution of the allar cartillages by a rhinoplasty with an external incision - Ishida, Jorge (1995)
Presentation of 62 cases of secondary nasal deformities treated by external incision. Several types of endonasal deformities were observed, properly classified and repaired. When excessive ressection was observed, local cartillage graft, septonasal or conchal types were employed.